Increasing Competitiveness of Chicken and Fillet Entrepreneurs in Lampung Through Marketing & Financial Digitalization Assistance - Fajar Gustiawaty Dewi; Kiagus Andi; Lindrianasari; Rindu Rika Gamayuni (Jurnal Sinergi, 2022)
The Covid-19 pandemic has dealt a hard blow to many businessman, especially SMEs. Restrictions on individual mobility have caused many traditional SMEs to go out of business because they are unable to adapt to existing changes. The Service Team took the initiative to provide assistance to affected SMEs partners by providing digital marketing assistance to increase business turnover and profit as well as an introduction to financial management. Frozen Food business is one type of business that is popular among the public, especially in Bandarlampung City. It is hoped that through digital marketing assistance, SMEs can adapt and be more agile in capturing the magnitude of business opportunities in the digital world, so that they are no longer limited to the environment around the location. Furthermore, financial management aims to make SMEs partner wiser in controlling the company's operational financial flows. We will also introduce SMEs partner to digital wallet channels and funding channels from financial institutions and banks. Keywords: Frozen Food, SMEs, Digital Marketing, Financial Management